Transcriptomic and phenotype analysis revealed the role of rpoS in stress resistance and virulence of a novel ST3355 ESBL-producing hypervirulent Klebsiella pneumoniae isolate - Zhou, Yi; Cheng, Yue; Ma, Tianyou; Wang, Jun; Li, Shaoru; Wang, Jingdan; Han, Lei; Hou, Xinyao; Ma, Xinxin; Jiang, Sijin; Li, Pu; Lv, Jia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
An extended spectrum beta-lactamase (ESBL)-hypervirulent Klebsiella pneumoniae (HvKP) strain HKE9 was isolated from blood in an out-patient. The effect of global regulatory factor RpoS on antimicrobial resistance, pathogenicity and environmental adaptability was elucidated. HKE9 is a novel ST3355 (K20/O2a) hypervirulent strain with positive string test, and resistant to cephems except cefotetan. It has a genome size of 5.6M, including 2 plasmids. There had CTX-M-15 in plasmid 2, and only ompk37 was found in chromosome. HKE9 could produce bacteria siderophores, and genes of enterobactin, yersiniabactin, aerobactin and salmochelin have been retrieved in genome. As a global regulatory factor, knockout of rpoS did not change antimicrobial resistance, hemolytic phenotype, while increased the virulence to Galleria mellonella larvae and showed higher viscosity. Moreover, rpoS knockout can increase bacterial competitiveness and cell adhesion ability. Interestingly, HKE9-M-rpoS decreased resistance to acidic pH, high osmotic pressure, heat shock and ultraviolet, and became sensitive to disinfectants (H2O2, alcohol and sodium hypochlorite). Although there had 13 Type 6 secretion system (T6SS) core genes divided into 2 segments with tle1 between segments in chromosome, transcriptome analysis showed rpoS negatively regulated T4SS located on plasmid 2, type 1 and type 3 fimbriae; positively regulate genes responsible for acidic response, hyperosmotic pressure, heat shock, oxidative stress, alcohol and hypochlorous acid metabolism, quorum sensing. Here, this novel ST3355, ESBL-HvKP strain HKE9 may spread via various clonal types. The important regulation effect of rpoS is the enhanced tolerance and resistance to environmental stress and disinfectants, which may be at the cost of reducing virulence and regulated by T4SS.